Selfish Nodes Detection Mechanism In Wireless Mesh Networks - Kai, Chong Zan (2010)
This thesis presents a robust packet drop attack detection protocol (named as Separation of Detection Authorities or SDA) that is aware of both DSNs and SSNs in the network. SDA uses a power-decentralised architecture; that is, the authorities are separated to a few entities such that no single entity is able to make adjudication unilaterally. The idea is commonly known as Separation of Powers as well.